THE ROLE OF COMMUNITY LEADER IN DEVELOPING THE ACTIVITY OF TUNAS MANDIRI EARLY CHILDHOOD EDUCATION RW (HAMLET.) 27 PADALARANG SUBDISTRICT, WEST BANDUNG - Tita Rosita (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2019)
The Implementation of Early Childhood Education (ECD) is to optimally grow, develop and foster the full potential of early childhood. So it could form basic behaviors and abilities of children in accordance with the stage of development in favor of having per preparation to enter further education and achieve the objective of education. In reality,  the implementation of ECD in the community is not maximal that caused by various factors. One of the issues has been suffered by TUNAS MANDIRI ECD located at RW (Hamlet) 27, Padalarang subdistrict, West Bandung. For 11 years TUNAS MANDIRI ECD has not shown a significant Since it established in 2007,  in other words, the learning process goes flat. But, in early 2017 and last 2018, this ECD shows an improvement. Therefore, this research is conducted by determining the research question; how the Community Leader in fostering TUNAS MANDIRI ECD in Padalarang Indah Regency, Padalarang, West Bandung. This research uses a descriptive qualitative method, with interviews and observation as a data collection technique. All data was taken from Community Leader, teacher of ECD, and the educators. There are four questions that answered by this research; How was the initial condition of the school, why this school did not show any progress for 11 years since it established, what factor that initiate the development in 2017 and what progress that achieved in 2017. As the result, the initial situation of this school are; having 30 students, 6 teacher, and educators. As a classroom, the ECD occupies an empty house. And for 11 years it did not develop due to the influence of passive community leaders, none of the teachers and educators were graduated from Early Childhood major. It means that the competence is not as it required, yet they follow various seminar, training, and HIMPAUDI Activity. The development since 2017 is due to the very responsive role of the head of the hamlet by having a clear mission to make this ECD as the most advance ECD in Padalarang.